1990
DOI: 10.1016/0025-3227(90)90003-3
|View full text |Cite
|
Sign up to set email alerts
|

Modification of a linear bar-trough system by a standing edge wave

Abstract: Bauer, B.O. and Greenwood, B., 1990. Modification of a linear bar-trough system by a standing edge wave. Mar. Geol.,.Detailed fluid motions and bathymetric changes in the lacustrine nearshore zone at Wymbolwood Beach, Georgian Bay, Canada were monitored during storms to test theoretical postulates about the importance of low-frequency wave motions to nearshore circulation of water and sediments. Eighteen continuous-resistance wave staffs and two electromagnetic current meters were deployed along one shore-norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
13
2

Year Published

1991
1991
2019
2019

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 44 publications
(68 reference statements)
4
13
2
Order By: Relevance
“…Previous studies have confirmed the generation of edge waves by storms both in this particular environment (e.g. Bauer and Greenwood, 1990) and elsewhere (e.g. Huntley.…”
Section: Discussionsupporting
confidence: 54%
“…Previous studies have confirmed the generation of edge waves by storms both in this particular environment (e.g. Bauer and Greenwood, 1990) and elsewhere (e.g. Huntley.…”
Section: Discussionsupporting
confidence: 54%
“…Thus, there was also a distinct lag in the infragravity wave transport compared to the gravity wave transport. Certainly, infragravity energies became dominant in the wave and current spectra in a manner similar to the lag that had previously been noted by Bauer and Greenwood (1990) in a barred system in Georgian Bay (an arm of Lake Huron).…”
Section: Contributions Au Taux De Transport En Biais Net à 23h15 Le supporting
confidence: 59%
“…Many studies have linked the coastal morphology, in particular the positions and shape of bars, to the spatial scales of lf waves. The length scale of standing waves measured in field conditions has been shown to fit well to the cross-shore spacing of bars (Aagaard, 1990;Bauer and Greenwood, 1990;Aagaard and Greenwood, 1994; among others). This has been interpreted as a sediment particle movement from standing long wave nodes to antinodes when the dominant sediment transport mode was suspended load (Bowen, 1980;Holman and Bowen, 1982).…”
mentioning
confidence: 81%
“…This has been interpreted as a sediment particle movement from standing long wave nodes to antinodes when the dominant sediment transport mode was suspended load (Bowen, 1980;Holman and Bowen, 1982). Bauer and Greenwood (1990) and Aagaard and Greenwood (1994) have shown experimental evidence of such a mechanism. However drift velocities in the bottom boundary layer beneath standing waves are generally assumed to be small compared to lf and hf wave orbital motions and mean currents (Aagaard and Greenwood, 2008).…”
Section: -Introductionmentioning
confidence: 99%